ANALYSIS OF NEEDS FOR THE DEVELOPMENT OF A TRAINING MODEL BASED ON HIGH ORDER THINKING SKILLS (HOTS) - Aminuddin, Rosihan; Syahrul, Syahrul; Idkhan, Andi Muhammad (Jurnal Vokasi Keteknikan, 2025)
This study aims to analyze the need to develop a training model based on Higher Order Thinking Skills (HOTS) in electrical training. HOTS is a high-level thinking skill that includes analysis, evaluation, and creation, which is very important in the world of education and industry. The research method used is a quantitative approach with a survey technique through questionnaires distributed to respondents involved in the implementation of electrical training. The results show that the use of the training model by lecturers is still very limited, with only 15% of lecturers actively using the training model, 25% of lecturers occasionally using it, and 60% of lecturers not using the training model at all. In addition, the results of the questionnaire also showed that only 27% of the training materials had been integrated with the concept of HOTS, which showed that the majority of the materials still did not accommodate the higher-order thinking approach. These findings indicate that the development of a more structured HOTS-based training model is needed to improve the effectiveness of electrical training. Efforts to improve the competence of lecturers in implementing the HOTS training model and the integration of the HOTS concept in training materials are crucial aspects in the development of critical, analytical, and creative thinking skills of trainees.